The Role of the Nurse in Preventing Infection: Practices and Strategies for Effective Infection Control (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Infection prevention and control (IPC) are fundamental pillars of patient safety and healthcare quality. Nurses, who are present at the bedside 24/7, are in a unique position to implement and sustain IPC practices. This study aims to explore the critical responsibilities of nurses in infection control, analyze the impact of nurse-led interventions on reducing healthcare-associated infections (HAIs), and evaluate challenges and enablers to effective IPC practices. The study synthesizes data from international guidelines, peer-reviewed literature, and hospital case studies. The findings highlight the need for comprehensive education, institutional support, and systemic accountability to empower nurses in their infection control role.